Systematic Review of Case Control Studies: Durasi Paparan, Jenis Serat Asbes, dan Jenis Pekerjaan Berhubungan dengan Keganasan Paru pada Pekerja di Tempat Kerja dan Industri - Putri Qintara Choirunnisa; Rakanda Muhammad Naufal Pratomo; Siti Annisa Devi Trusda; Gemah Nuripah (UNISBA Press, 2022)
Abstract. Lung malignancy is the high leading causes of cancer death in the world. In 2020, there were 95,735 cases of lung cancer in Southeast Asia and 28,716 cases in Indonesia, the highest in Southeast Asia. The incidence of mesothelioma worldwide has increased since the mid-20th century. Many big impacts from a worker in asbestos factory. Asbestos is an occupational carcinogens. Approximately 125 million people in the world are exposed to asbestos in the workplace. Asbestos is a group of naturally fibrous minerals. The purpose of study was determine the relationship between duration of exposure, type of asbestos fiber, and type of work with lung malignancy of workers in the workplace and industry. Systematic Review is the study method, searching articles from the PubMed, Springer Link, Science Direct, and ProQuest with the keywords Asbestos AND Occupational exposure AND Lung cancer AND Case-control study in 2010-2021. There are 984 inclusion criteria articles with 13 eligible criteria articles. The results of the exposure duration was more than 20-30 years (OR 13.9 99% CI 7.2–27.0), chrysotile asbestos (OR 9.3 95% CI 5.4–16,1), work in the workplace and industry (OR 1.26 95% CI 0.98–1.62), has an associated risk of lung malignancy. Abstrak. Keganasan paru merupakan penyebab kematian tertinggi akibat kanker yang paling tinggi di dunia. Pada 2020, Asia Tenggara terdapat 95.735 kasus dan di Indonesia terdapat 28.716 kasus yang merupakan tertinggi se-Asia Tenggara. Kejadian mesothelioma di seluruh dunia meningkat sejak pertengahan abad ke-20. Banyak dampak besar dari seorang pekerja di pabrik asbes. Menurut WHO, asbes adalah salah satu karsinogen kerja. Sekitar 125 juta orang di dunia terpapar asbes di tempat kerja. Asbes merupakan sekelompok mineral berserat alami. Tujuan penelitian ini untuk mengetahui hubungan antara durasi paparan, jenis serat asbes, dan jenis pekerjaan dengan keganasan paru pada pekerja di tempat kerja dan industri. Penelitian ini menggunakan metode Systematic Review, dengan mencari artikel dari database PubMed, Springer Link, Science Direct, dan ProQuest dengan kata kunci Asbestos AND Occupational exposure AND Lung cancer AND Case-control study dalam rentang tahun 2010-2021. Terdapat 984 artikel kriteria inklusi dengan 13 artikel kriteria eligible. Hasil durasi paparan lebih dari 20-30 tahun dengan OR 13,9 99% CI 7,2–27,0, jenis serat asbes chrysotile dengan OR 9,3 9%% CI 5,4–16,1, pekerjaan di tempat kerja dan industri dengan OR 1,26 95% CI 0,98–1,62, memiliki hubungan risiko keganasan paru.